Acoustic analysis to monitor implant seating and early detect fractures in cementless THA: An in vivo study. Issue 6 (12th September 2020) - Goossens, Quentin; Pastrav, Leonard; Roosen, Jorg; Mulier, Michiel; Desmet, Wim; Vander Sloten, Jos; Denis, Kathleen
Abstract: The initial stability of cementless total hip arthroplasty (THA) implants is obtained by an interference fit that allows osseointegration for a long term secondary stability of the implant. Yet, finding the insertion endpoint that corresponds to an appropriate initial stability is currently often based on a number of subjective experiences of the orthopedic surgeon, which can be challenging. In order to assist the orthopedic surgeons in their pursuit to find this optimal initial stability, this study aims to determine whether the analysis of sound that results from the implant insertion hammer blows can be used to objectively monitor the insertion process of cementless THA implants. An in vivo study was conducted. The experimental results revealed vibro‐acoustic behavior sensitive to implant seating, related to the low frequency content of the response spectra. This sensitive low‐frequency behavior was quantified by a set of specific vibro‐acoustic features and metrics that reflected the power and similarity of the low‐frequency response. These features and metrics allowed monitoring the implant seating and their convergence agreed well with the endpoint of insertion as determined by the orthopedic surgeon. Intraoperative fractures caused an abrupt and opposite change of the vibro‐acoustic behavior prior to the notification of the fracture by the orthopedic surgeon. The observation of such an abrupt change in the vibro‐acoustic behavior can be an important early warning for loss of implant stability. The presented vibro‐acoustic measurement method shows potential to serve as a decision supporting source of information as it showed to reflect the implant seating.